Clinical study of early rehabilitation training combined with negative pressure wound therapy for the treatment of deep partial-thickness hand burns - Liu, Canbin; Xie, Hongteng; Wei, Pei; Gong, Teng; Wu, Guohua; Xu, Zhaorong; Chen, Shun (Frontiers in Surgery, 2023)
Objective To explore the clinical effect of early rehabilitation combined with negative pressure wound therapy (NPWT) in the teatment of deep partial-thickness hand burn. Methods Twenty patients with deep partial-thickness hand burn were randomly divided into experimental group (n=10) and control group (n=10). In experimental group, the early rehabilitation cimbined with NPWT were performed, including intraoperative plastic brace, postoperative position, and exercise therapy during NPWT process early after surgery. Routine rehabilitation and NPWT were conducted in the control group. Hand function was evaluated before treatment, after NPWT removal and 4 weeks after rehabilitation, including hand joint total active motion (TAM) and brief Michigan hand function profiles (bMHQ). Results The TAM and bMHQ scores did not differ between the two groups before treatment, and they were both improved after treatment. What’s more, the improvement of angle change was much better in the experimental group than that in control group, as well as the excellent rate of TAM (p<0.05). The bMHQ scores in the experimental group was also significantly higher (p<0.05). Conclusion Hand function was significantly improved in deep partial-thickness hand burn when treated by early rehabilitation combined with NPWT.